2023
DOI: 10.1177/2333794x231191982
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Neonatal Birth Trauma in Ethiopia: Systematic Review and Meta-Analysis

Abstract: Introduction. Neonatal death is still alarming in low-income countries including Ethiopia, accounts 30 death per 1000 alive births. Birth trauma is the second most common contributing factors for the death. Nevertheless, there is no aggregate evidence on the prevalence and patterns of neonatal birth trauma in Ethiopia. Therefore, this study aimed to assess the pooled prevalence and patterns of neonatal birth trauma in Ethiopia. Methods. Searching databases including PubMed, MEDLINE, Popline, SCOPUS, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The search yielded a single systematic review, which only reported a pooled prevalence and the most common neonatal birth trauma in Ethiopia. 21 This review does not assess the predictors of neonatal birth trauma and included only neonatal birth trauma that happened at health institutions without considering home delivery. However, there is no current or underway systematic review in Africa on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…The search yielded a single systematic review, which only reported a pooled prevalence and the most common neonatal birth trauma in Ethiopia. 21 This review does not assess the predictors of neonatal birth trauma and included only neonatal birth trauma that happened at health institutions without considering home delivery. However, there is no current or underway systematic review in Africa on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…In the West medical literature, trauma of the newborn affects 20-30 babies per 1000 live births [5,6]. In Africa, statistics are not available, but studies from Mali and Morocco reveal a frequency of 0.68% and 0.26% respectively [7][8][9]. The main risk factors are fetal macrosomia, instrumental delivery, fetal breech presentation, parity and maternal age [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%